The Role of the Community in Supplementary Feeding Programs as a Measure to Prevent Stunting in Dadirejo Village - Calista Meryna Putri; Ferani Mulianingsih (JURNAL KESMAS DAN GIZI (JKG), 2026)
Stunting remains a major public health issue frequently found among young children and is closely associated with chronic malnutrition. The Supplementary Feeding Program is one of the key interventions implemented at posyandu to prevent stunting by providing nutritionally balanced foods for children under five. This study aims to describe the community’s role in PMT implementation in Dadirejo Village, particularly the involvement of health cadres, village midwives, and mothers of young children. A descriptive qualitative design was used, employing observations, questionnaire-based interviews, and in-depth interviews. The findings show a significant increase in child attendance (from 62% to 93%) and maternal participation (from 7 to 22 mothers). Mothers also expressed positive perceptions, with 72.41% stating that PMT improves nutritional status and 62.07% reporting that menus are appropriate. Cadres and midwives evaluated the implementation positively, although facilities, nutrition education, and parental involvement still require strengthening. Overall, PMT is considered beneficial and effective in supporting stunting prevention, yet enhanced community participation and improved nutrition services remain essential priorities.